(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: The aim of this study was to investigate the impact of employment status on self-reported health in Gävleborg County. Methods: The study used data from the 2010 Health in Equal terms survey, a cross-sectional survey carried out in Gävleborg County in Sweden. A total of 4,245 individuals, aged 16–65 years were included in the analysis. Descriptive and logistic regression analyses were used to assess the relationship between employment status and self-reported health Results: People who were outside the labour market had odds of poor health of 2.64 (Cl 2.28–3.05) compared to their employed counterparts. Controlling for other covariates reduced the risk slightly to 2.10 (1.69-2.60) but remained statistically significant. In addition, other variables were associated with self-reported poor health Conclusion: This study found a statistically significant association between being outside the labour market and poor self-reported health. The relation was explained partially by socio-economic and demographic variables. Further studies are needed to further investigate the observed relationships. Longitudinal studies are needed to further investigate the observed relationship. Policy-makers within the Gävleborg County need to pay attention to the health status of those out of work, especially during times of combined economic and labour market fluctuations. Results of the study suggest the need to pay attention to the health status of those outside the labour market especially during times of economic hardship.